Transnational Cultures, Transcultural Nations: The Contribution of Women Writers of Afro-Caribbean Origin to Multicultural Canada - Alonso-Breto, Isabel (SARE: Southeast Asian Review of English, 2017)
Until well into the second half of the 20th century, Canada was still heavily burdened with the task of outlining the contours of a national culture distinct from those of the so-called 'Founding Nations.' In literary studies, for instance, works seminal for the configuration of a national literary imaginary and canon were being published as late as 1971 in the case of Northop Frye's The Bush Gardens: Essays on the Canadian Imagination (a compilation of articles written between 1943 and 1969), and 1972 in that of Margaret Atwood's Survival: A Thematic Guide to Canadian Literature. After more than four decades, Canada has not overcome the need to imagine itself as a nation. Janice Kulik Keefer has emphasized the Mosaic's perennial 'need to keep nationalism enthroned in [its] collective psyche' (293), an obsession whose cause is manifold.